POLIFARMASI DAN PENGOBATAN YANG KURANG TEPAT DALAM FARMAKOTERAPI STROKE, BAGAIMANA SPESIALIS NEUROLOGI MENSIKAPINYA: POLYPHARMACY AND INAPPROPIATE MEDICATION IN STROKE PATIENT: WHAT NEUROLOGIST SHOULD AWARE? - Pambudi, Pagan; Steven (PERDOSNI, 2025)
Polypharmacy and inappropriate medication use are often found in elderly stroke patients and have negative consequences such as less than optimal functional outcomes, increased incidence of drug side effects, increased treatment time and costs. However, polypharmacy seems difficult to avoid in stroke patients where there are many underlying comorbidities that require pharmacotherapy. Neurology specialist doctors as doctors responsible for patients need to manage polypharmacy and inappropriate use of drugs in order to achieve treatment goals, namely optimal functional outcomes and patient safety at an efficient cost.